2016
DOI: 10.1021/acs.jpcb.6b08883
|View full text |Cite
|
Sign up to set email alerts
|

Folding of a Zinc-Finger ββα-Motif Investigated Using Two-Dimensional and Time-Resolved Vibrational Spectroscopy

Abstract: Small proteins provide good model systems for studying the fundamental forces that control protein folding. Here, we investigate the folding dynamics of the 28-residue zinc-finger mutant FSD-1, which is designed to form a metal-independent folded ββα-motif, and which provides a testing ground for proteins containing a mixed α/β fold. Although the folding of FSD-1 has been actively studied, the folding mechanism remains largely unclear. In particular, it is unclear in what stage of folding the α-helix is formed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 58 publications
1
6
0
Order By: Relevance
“…The lowest OM action folding pathway is consistent with a recent experiment 57 published after the submission of this work, where the early formation of C-terminal α-helix is observed to be followed by the concurrent formation of the β-hairpin and hydrophobic contacts. A comparison of the root mean square deviation values indicates that the α-helix approaches to the native structure earlier than the β-hairpin.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The lowest OM action folding pathway is consistent with a recent experiment 57 published after the submission of this work, where the early formation of C-terminal α-helix is observed to be followed by the concurrent formation of the β-hairpin and hydrophobic contacts. A comparison of the root mean square deviation values indicates that the α-helix approaches to the native structure earlier than the β-hairpin.…”
Section: Resultssupporting
confidence: 90%
“…After our manuscript was submitted, it came to our attention that Meuzelaar and co-workers reported that the folding of FSD-1 occurs via an intermediate state where only the α-helix is formed 57 . After this intermediate state, the β-hairpin and hydrophobic contacts form.…”
Section: Resultsmentioning
confidence: 99%
“…Time-resolved nonlinear infrared spectroscopy has the advantage of being able to monitor vibrational energy dissipation pathways, as well as structural dynamics of molecular systems in condensed phases. Infrared pump–probe experiments under the so-called magic-angle polarization condition can provide vibrational lifetime information on a given vibrational mode. How vibrational energy relaxes after excitation, whether it is through an intramolecular vibrational energy redistribution channel or through intermolecular energy transfer by interacting with the solvent environment, can be understood on the basis of time-resolved vibrational measurements. Time-resolved infrared spectroscopies, in particular IR pump–IR probe and two-dimensional infrared (2D IR) spectroscopies, have the advantage of simultaneously monitoring vibrational energy dissipation channels and molecular structural dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular dynamics (MD) simulations offer an atomic-level description but are unsuitable for slower dynamical processes as a result of the computational cost and complexity (Figure ). ,,, Structurally heterogeneous proteins like IDPs and proteins with IDRs are dynamic at the same time which can intrinsically sample a multitude of diverse structures, thus providing a robust data set for testing structural refinement methodologies and kinetic pathway sampling using time-resolved techniques with molecular models.…”
Section: Introductionmentioning
confidence: 99%
“…Time scales for protein dynamics grouped by technique. ,,, Relevant protein time scales are plotted vs the number of residues for the system of interest for studies done using MD (purple), TRXSS (green), IR (blue), and trp-fluorescence (orange). MD studies are primarily located around smaller proteins and shorter time scales.…”
Section: Introductionmentioning
confidence: 99%